2010
DOI: 10.4061/2010/749061
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Impact of the Regulation of the Brain 2-Oxoglutarate Dehydrogenase Complex by Synthetic Phosphonate Analog of 2-Oxoglutarate: Implications into the Role of the Complex in Neurodegenerative Diseases

Abstract: Decreased activity of the mitochondrial 2-oxoglutarate dehydrogenase complex (OGDHC) in brain accompanies neurodegenerative diseases. To reveal molecular mechanisms of this association, we treated rats with a specific inhibitor of OGDHC, succinyl phosphonate, or exposed them to hypoxic stress. In males treated with succinyl phosphonate and in pregnancy-sensitized females experiencing acute hypobaric hypoxia, we revealed upregulation of brain OGDHC (within 24 hours), with the activity increase presumably repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Some data demonstrated that malfunction of the OGDHC associated with mitochondrial dysfunction might be a crucial point in the pathogenesis of depression [33]. Consistent with this finding, the stimulation of the brain OGDHC complex by a synthetic analog of 2-oxoglutarate upregulated the activity of this enzymatic complex and affected behavioral changes, which were expressed as an increase in exploratory activity and diminished anxiety behavior in rats [32]. Based on this observation, it may be postulated that the ability of tianeptine to upregulate the OGDHC in the hippocampus may have a beneficial impact on the brain metabolism and on the behavioral disturbances observed in prenatally stressed animals.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Some data demonstrated that malfunction of the OGDHC associated with mitochondrial dysfunction might be a crucial point in the pathogenesis of depression [33]. Consistent with this finding, the stimulation of the brain OGDHC complex by a synthetic analog of 2-oxoglutarate upregulated the activity of this enzymatic complex and affected behavioral changes, which were expressed as an increase in exploratory activity and diminished anxiety behavior in rats [32]. Based on this observation, it may be postulated that the ability of tianeptine to upregulate the OGDHC in the hippocampus may have a beneficial impact on the brain metabolism and on the behavioral disturbances observed in prenatally stressed animals.…”
Section: Discussionmentioning
confidence: 58%
“…Importantly, our data demonstrated that chronic tianeptine administration in prenatally stressed offspring increased the expression of a component of the 2-oxoglutarate dehydrogenase complex (OGDHC). The OGDHC comprises multiple copies of three catabolic components, the action of which is required for an important regulatory step in the mitochondrial Krebs cycle (the oxidative decarboxylation of 2-oxoglutarate, which generates energy in the form of NADH and the macroergic compound succinyl-CoA) [32]. Some data demonstrated that malfunction of the OGDHC associated with mitochondrial dysfunction might be a crucial point in the pathogenesis of depression [33].…”
Section: Discussionmentioning
confidence: 99%
“…This response may contribute to preconditioning effects. These and other data suggest that the action of the phosphonate analogs of 2‐oxoglutarate on OGDHC may provide the mechanistically defined model of chemically induced hypoxia. Currently, such models employ cyanide to inhibit respiration and iodoacetate to inhibit glycolysis .…”
Section: Modeling the Impaired Function Of Neuronal And Brain Ogdhc Bmentioning
confidence: 73%
“…Interestingly, low doses of SP induced preconditioning effects in animals exposed to hypoxia, which was associated with an increase in their brain OGDHC activity. The increase in OGDHC was ascribed to a compensatory response resulting from OGDHC inhibition by SP [36,149,150]. In this regard, a temporary increase in neuronal ATP which was observed under low SP doses in situ, may contribute to the preconditioning in vivo.…”
Section: Phosphonate Analogs Of 2-oxo Acids As Tools To Specifically mentioning
confidence: 97%
See 1 more Smart Citation